2009
DOI: 10.1016/j.humimm.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening of human T-cell epitopes in influenza A virus reveals a broad spectrum of CD4+ T-cell responses to internal proteins, hemagglutinins, and neuraminidases

Abstract: We performed a genome-wide screening for T cell epitopes using synthetic peptides that encompass all of the influenza A viral proteins, including subtype variants for hemagglutinin (HA) (H1, H3 and H5) and neuraminidase (NA) (human and avian N1 and N2) proteins, based on the sequence information of recently circulating strains. We found a total of 83 peptides, 54 of them novel, to which specific T cells were detectable in IFN-γ ELISPOT assays using peripheral blood mononuclear cells from four healthy adult don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 39 publications
1
65
1
Order By: Relevance
“…It seems that HA is the primary target of IAV-specific CD4 ϩ T cell responses. A recent genomewide T cell epitope screen using synthetic peptides found that HA and M1 contained more CD4 ϩ T cell epitopes, which seemed to support the above statistics (9). However, an earlier study found that M1 and NP, not HA, were the major targets of IAV-specific CD4 ϩ T cells (10), and another found that PB1 was the major target for both CD4 ϩ and CD8 ϩ T cell responses (11).…”
Section: Munodominant Cd8mentioning
confidence: 92%
See 1 more Smart Citation
“…It seems that HA is the primary target of IAV-specific CD4 ϩ T cell responses. A recent genomewide T cell epitope screen using synthetic peptides found that HA and M1 contained more CD4 ϩ T cell epitopes, which seemed to support the above statistics (9). However, an earlier study found that M1 and NP, not HA, were the major targets of IAV-specific CD4 ϩ T cells (10), and another found that PB1 was the major target for both CD4 ϩ and CD8 ϩ T cell responses (11).…”
Section: Munodominant Cd8mentioning
confidence: 92%
“…Thus, the antigen specificity of IAV-specific CD4 ϩ T cell responses is still controversial. Moreover, due to the limited availability of peripheral blood mononuclear cells (PBMCs), the above-mentioned studies (9)(10)(11) used peptide pools to screen T cell responses and, as a result, did not determine the immunodominance hierarchy at the single-epitope and HLA levels in each individual.…”
Section: Munodominant Cd8mentioning
confidence: 99%
“…However, there is substantial evidence suggesting that broadly neutralizing non-HI antibodies may also play an important role. 8,9 As far as T lymphocyte responses are concerned, several studies have shown that human CD4 C and CD8 C T cell responses typically cross-react to multiple influenza strains and subtypes, and mainly target internal components of the virus, [10][11][12] and that both CD4 C and CD8 C T cells may independently protect humans from infection or disease. 13,14 Evidence from elderly subjects, in whom the antibody response is quantitatively poor compared to adults, 15 suggests that CD4 C and CD8 C T cell responses may correlate better with protection.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid aggregation, only the soluble domain of this protein was fused to VP2C, which came in two variations, VP2C-M1-I and VP2C-M1-II. The M1-I domain contains several epitopes (Figure 1.2) comprising several HLA supertypes such as A2, A3, B44, and B12 (Adar et al 2009;Alexander et al 2010;Assarsson et al 2008;Babon et al 2009;Liu et al 2013;Reemers et al 2012), which would be good for broader cross-protection (Brown and Kelso 2009) and wider population coverage (Sette and Sidney 1998). VP1:VP2C-M1-II was not pursued further due to complication in purification related to the presence of the previously reported aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…M1-II consists of M1-I in addition to the rest of the downstream amino acids of the N-terminal domain. Beside M158-66 epitope (further termed IT1 in this thesis), other epitopes covering a number of HLAs (Alexander et al 2010;Assarsson et al 2008;Babon et al 2009;Lee et al 2008;Liu et al 2013;Tan et al 2010;Wang et al 2007) (Berthoud et al 2011) Figure 1.2 M1 protein soluble domain and epitope distribution. 3D structure of influenza M1 soluble domain (PDB 1EA3SID) (A).…”
Section: ) This Epitope Is Conservedmentioning
confidence: 99%